2014
DOI: 10.1186/1471-2148-14-71
|View full text |Cite
|
Sign up to set email alerts
|

Inactive alleles of cytochrome P450 2C19 may be positively selected in human evolution

Abstract: BackgroundCytochrome P450 CYP2C19 metabolizes a wide range of pharmacologically active substances and a relatively small number of naturally occurring environmental toxins. Poor activity alleles of CYP2C19 are very frequent worldwide, particularly in Asia, raising the possibility that reduced metabolism could be advantageous in some circumstances. The evolutionary selective forces acting on this gene have not previously been investigated.We analyzed CYP2C19 genetic markers from 127 Gambians and on 120 chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…The increased-activity CYP2C19*17 allele frequency of the Afro-Caribbean population is consistent with its high frequency in the West African Gambia population (23.0 %) (Janha et al, 2014), which is in accordance to the predominant Western African origin of the African diaspora to the Americas (Madrigal, 2006). The ascertainment of CYP2C19 gUMs by genotyping of the CYP2C19*17 allele has only been performed in other two Latin American admixed populations from Brazil and Ecuador (26.8 and 41.4 %, respectively) (Santos et al, 2011;Vicente et al, 2014), and both frequencies are higher than that of the Costa Rican admixed population (17.7 %; P<0.05).…”
Section: Discussionsupporting
confidence: 73%
“…The increased-activity CYP2C19*17 allele frequency of the Afro-Caribbean population is consistent with its high frequency in the West African Gambia population (23.0 %) (Janha et al, 2014), which is in accordance to the predominant Western African origin of the African diaspora to the Americas (Madrigal, 2006). The ascertainment of CYP2C19 gUMs by genotyping of the CYP2C19*17 allele has only been performed in other two Latin American admixed populations from Brazil and Ecuador (26.8 and 41.4 %, respectively) (Santos et al, 2011;Vicente et al, 2014), and both frequencies are higher than that of the Costa Rican admixed population (17.7 %; P<0.05).…”
Section: Discussionsupporting
confidence: 73%
“…In addition, a recent study of 2203 African Americans (Gordon et al, 2014) found that CYP2C19 had the highest number of putative novel functional variants compared with 11 other drug metabolizing CYP genes. This result was interesting because it was recently reported that the CYP2C19*2 nonfunctional allele may have been positively selected in human evolution (Janha et al, 2014), and that inactivation of CYP2C19 might have afforded some survival advantage. Conversely, because CYP2C19 loss-of-function alleles confer increased risks for serious adverse cardiovascular events among clopidogrel-treated patients, Clinical Pharmacogenetic Implementation Consortium guidelines were issued for CYP2C19 genotype-directed drug therapy (Scott et al, 2013).…”
Section: Introductionmentioning
confidence: 70%
“…Second, we used extended haplotype homozygosity statistics and uncovered significant evidence that the haplotypes with rs12769205 alone (CYP2C19*35) and with rs4244285 on CYP2C19*2 have undergone positive selection, and that natural selection was not limited to YRI but was seen across African populations, having probably arisen in earlier human ancestors from which all other groups of Africans descended. Notably, the magnitude of evolutionary pressure for both haplotypes with rs12769205 was as great as that exerted on the human genome by infectious diseases (Janha et al, 2014), and implies that rs12769205 on both haplotypes confers an evolutionary advantage. Indeed, the signature of positive selection on the haplotype with rs12769205 alone (CYP2C19*35) reinforces that this polymorphism has a significant functional effect independent of rs4244285.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations